PERANCANGAN MENGGUNAKAN PROGRAM VISUAL BASIC 6 UNTUK PENGOLAHAN LIMBAH CAIR DENGAN AERATED LAGOON - Subagio, Heru (Jurnal Rekayasa Lingkungan)
Dimension of aerated lagoon and another unit operation in this system can easy counted by this software. This software uses VISUAL BASIC6 computer language. Waste water treated have pH between 6.5 and 8, biodegradable waste and BOD less than 500. This waste water treatment need big fi eld and separate far away from people because bad smelt.This software also will guess BOD output and fl ow diagram this system.Key words: aerated lagoon, biodegradable, BOD, pH